Investigating the Prevalence of Latent Tuberculosis among Healthcare Workers of Major Hospitals of Ahvaz, Iran - Bavarsad, Amir Hooshang; Idani, Esmaiel; Shoushtari, Maryam Haddadzadeh (Journal of Intellectual Disability - Diagnosis and Treatment, 2019)
Background and Objective: Healthcare and laboratory workers in hospitals have a higher exposure to hospital-acquired infections (HAIs) than the general populations. Tuberculosis (TB) infection is a common HAI that is communicated from the patients with TB admitted or hospitalized in the healthcare centres. This study aims to determinate the incidence and prevalence of latent TB infection among healthcare workers in the major Hospitals in Ahvaz, Khuzestan province, Iran. Methods: This is a case-control study conducted on healthcare workers diagnosed with TB between January 2010 to December 2017. The study population consisted of healthcare workers of the three major hospitals of Ahvaz, Khuzestan including Imam Khomeini Hospital, Golestan Hospital and Shafa Hospital. All subjects underwent Mantoux tuberculin skin test (TST) and after 48 to 72 hours the reaction was measured as the length of induration. The induration equal to or greater than 10 mm was considered as positive TB. Moreover, the subjects and controls were asked to complete a self-administered questionnaire on potential risk factors for TB. Results: Among 513 subjects, male and female subjects were respectively 186 and 327. Of all subjects, 67 subjects (male: 42; female: 25) showed positive TST (10 mm ≤ induration) and 275 subjects showed 5 mm >induration. There was a significant relationship between TST result and the workplace of the subjects. Gender showed no significant relationship with the TST result. Conclusion: All healthcare workers who are in direct contact with TB patients must undergo regular TB screening test and the workers should be trained for self-conducting TST.